2003
DOI: 10.1074/jbc.m308287200
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Deficits and Hyperactivity in Mice Lacking Smad4

Abstract: Smad4 is a central mediator of TGF-␤ signals, which are known to play essential roles in many biological processes. Using a Cre-loxP approach to overcome early embryonic lethality, we have studied functions of TGF-␤/Smad4 signals in the central nervous system (CNS). No obvious deficits were detected in mice carrying the targeted disruption of Smad4 in the CNS. The overall morphology of the hippocampus appeared normal. There was no change in the proliferation of neuronal precursor cells, nor in several forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 72 publications
4
60
1
Order By: Relevance
“…Consistent with results from previous pan-neuronal deletion of Smad4 (Zhou et al, 2003), we found no significant difference in hippocampal long-term synaptic plasticity between Smad4 KO mice and control mice. Smad4 KO mice showed both normal early-phase LTP and late-phase LTP in the CA1 region of hippocampus (Fig.…”
Section: Conditional Deletion Of Smad4 In the Mouse Forebrain Did Notsupporting
confidence: 81%
“…Consistent with results from previous pan-neuronal deletion of Smad4 (Zhou et al, 2003), we found no significant difference in hippocampal long-term synaptic plasticity between Smad4 KO mice and control mice. Smad4 KO mice showed both normal early-phase LTP and late-phase LTP in the CA1 region of hippocampus (Fig.…”
Section: Conditional Deletion Of Smad4 In the Mouse Forebrain Did Notsupporting
confidence: 81%
“…We cannot, however, rule out the possibility that a low level of BMP signaling is occurring that falls below the threshold of our phospho-Smad immunohistochemistry. Furthermore, condi-tional inactivation of the BMP signaling mediator Smad4 in postnatal animals results in Purkinje cell loss, suggesting that BMP signaling may be required for Purkinje cell maintenance (Zhou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of TGF-b family signaling by a reduction in Smad4 during embryogenesis is required for proper temporal and spatial development of granule progenitor cells (Fernandes et al 2012). However, inactivation of Smad4 in the mouse CNS results in a marked decrease in the number of Purkinje cells and parvalbumin-positive interneurons in the cerebellum (Zhou et al 2003). Taken together, members of the TGF-b family directly regulate various cell types in the cerebellum.…”
Section: Hindbrainmentioning
confidence: 99%